Guidelines for the Diagnosis and Treatment of Rosacea in China (2021 Edition)# - Rosacea Research Center, Chinese Society of Dermatology; Rosacea Professional Committee, Chinese Dermatologist Association; Heng Gu; Fei Hao; Wei He; Dan Jian; Zhe Jian; Xian Jiang; Qiang Ju; Xiao-Jing Kang; Wei Lai; Heng-Jin Li; Ji Li; et al. (Wolters Kluwer Health, 2021)
Abstract. Rosacea is a chronic inflammatory skin disease that primarily affects the centrofacial areas and mainly manifests as recurrent flushing and erythema. In recent years, there has been progress in the understanding of the diagnosis and treatment of rosacea. Therefore, a group of dermatological experts updated the guidelines based on the 2016 expert consensus statement on rosacea diagnosis and treatment in China. These new guidelines propose diagnostic criteria for rosacea at different sites to further standardize the diagnosis and treatment of rosacea in China.